Pengaruh Pendapatan Asli Daerah, Dana Perimbangan Dan Kinerja Keuangan Daerah Terhadap Alokasi Belanja Modal (Studi Empiris Pada Pemerintah Daerah Kabupaten/Kota di Provinsi Jawa Barat Tahun 2010-2014) - WIJAYANTI, YUNI; , Eny Kusumawati, S.E, M.M, Akt (2017)
The purpose of this study was to analyze influence of Local OwnRevenue, General Allocation Fund, Special Allocation Fund, Revenue Sharing Fund, Desentralitation Level, Regional Financial Independence level andRegional Financial Effectiveness Level towards the CapitalExpenditures at the regencies/ municipalities in the West JavaProvince from 2010 to 2014. This study is causality researches that have hypothesis testing nature. The population of this research is by using financial data from local governments Budget Realization Report in West JavaProvince from 2010 to 2014. Research sampling used purposive sampling technique and found 6regional and 2 cities, with 5 years of observation. The total sample studied was 40. The collected data was analyzed using classic assumption test and then do hypothesis test. Testing the hypotesis in this study using multiple regression analysis with t-test, F, and the coefficient of determination.Partial result of this hypothesis testing concluded that Local Own Revenue, Special Allocation Fund, and Regional Financial Independence level has positive influenceand significant impact on capital expenditure. While, Revenue Sharing Fund, General Allocation Fund, Desentralitation Level, and Regional Financial Effectiveness Levelhasn't affect the capital expenditures.